Interroger la promotion internationale de l’État de droit à l’aune de la détention avant jugement. L’exemple de la Côte d’Ivoire - Fischer, Bénédicte (Déviance et société, 2021)
Although the rule of law is established as an international standard, the historical origins of the concept have virtually disappeared, to the point whereby the rule of law is now often conceived of as something neutral, measurable by various indicators. However, building the rule of law assumes a certain type of state and a certain conception of the law, particularly on the criminal side. These inconvenient truths were raised in a survey conducted among several hundred defendants in the Ivory Coast. The findings highlight a criminal justice system that is disconnected from societal representation, practical norms, and the administrative organization that is crucial to its very existence. Through an action-research approach, a mixed methods analysis of the studys quantitative and qualitative data shows that despite the contemporary revision of norms, there is no systematic re-evaluation of pretrial detention. Following the principles of the rule of law, criminal justice reform aims to impose of standards which are disconnected from endogenous notions of law and justice, without considering the local realities of mediation processes. The focus on pretrial detention highlights the paradoxical nature of a criminal justice reform process that is totally dissociated from its administrative foundations.